Helicobacter pylori–Negative MALT Lymphoma Presenting as a Massive Recurrent Gastrointestinal Hemorrhage. (June 2020) - Harne, Prateek S.; Mukherjee, Samiran; Achufusi, Ted; Lowe, Dhruv; Manocha, Divey
Primary gastric lymphoma is rare, representing 5% of all primary gastric neoplasms. The presenting complaints of gastric mucosa-associated lymphoid tissue (MALT) lymphoma are usually nonspecific. However, life-threatening gastrointestinal bleeding from the stomach is unusual and sparsely reported. While studies reveal an indolent course, we present a case that presented with massive and recurrent hematemesis leading to hypovolemic shock secondary to endoscopically confirmed MALT lymphoma, which was treated with radiotherapy to achieve remission. She had no autoimmune diseases and tested negative for Helicobacter pylori . Our case emphasizes the importance of early diagnosis and timely intensive radiotherapy of a localized but aggressive gastric MALT lymphoma.